Strategy Formulation and Implementation for CV Pinanggih in Automation Business - Adi Nugroho, Anintyo; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2016)
Abstract - Based on Frost and Sullivan research result, Indonesia automation market will grow strongly over the forecast period (2014-2018). However, throughout 2014 and 2015, Pinanggih faces a various challenge from external and internal environment. Some of reasons are depreciation rupiah, Falling world crude oil prices and tight competition among of automation companies. Pinanggih net profit Decreased due to, no significant increase in sales, small profit margins, and swelled operating expenses. The objective of this research is to analyze the business environment of automation and make formulation and implementation strategy for CV Pinanggih to compete with other competitors, to penetrate and to add new customers in the end increase sales of the company in the next year. To analyze company current condition use strategic audit framework, the external and internal conditions. The results of external and internal environment become the basis of SWOT formulation. Corporate strategy analysis conducted using the SPACE Matrix and QSPM. To formulate Functional Strategy use TOWS Matrix. The conclusions are unstable the exchange rate, plus the loss of the market potential of the oil and gas industry greatly affects industrial automation. Tight competition among competitors and ineffective strategy used is not a significant impact on the company's growth. Pinanggih must formulate a new corporate strategy and new functional strategy.Â Keywords: Automation, decrease profit, Strategy Formulation